Molecular epidemiology of a carbapenem-resistant Serratia marcescens outbreak during the COVID-19 pandemic - da Rocha, Letícia Fernandes; Rodrigues, Grazielle Motta; de Oliveira, Gabriela Simões; Echevarria, Aymê Duarte; Wink, Priscila; Volpato, Fabiana; Berdichevski, Mayana; Lutz, Larissa; Pereira, Dariane Castro; Barth, Afonso Luís; Martins, Andreza Francisco (Frontiers in Microbiology, 2025)
IntroductionSerratia marcescens is a significant causative agent of hospital-acquired infections (HAIs), particularly in intensive care units (ICUs). Carbapenem resistance represents a major concern in HAI management, as carbapenem-resistant bacteria can trigger outbreaks in hospital settings. While molecular evaluation of outbreaks typically relies on pulse field gel electrophoresis (PFGE) or core genome multilocus sequence typing (cgMLST) methods, alternative rapid, reliable, and cost-effective methods for assessing clonal relatedness are needed.MethodsThis study aimed to characterize a carbapenem-resistant S. marcescens outbreak that occurred during the COVID-19 pandemic in a tertiary care hospital, using the flagellin gene as a single-locus sequence typing (SLST) method. In addition, we evaluated the genetic context of carbapenemase genes through whole-genome sequencing (WGS).ResultsAmong the 170 carbapenem-resistant Serratia marcescens isolates recovered, high resistance to gentamicin, ciprofloxacin, and cefepime was observed. The predominant carbapenemase gene detected by qPCR-HRM was blaKPC (92.2%). Phylogenetic analysis of the flagellin gene grouped the sequences into two distinct clades, with all outbreak-related blaKPC-positive S. marcescens isolates clustering within clade B. The blaKPC gene was carried on an IncP6 plasmid.DiscussionOur findings indicate that the flagellin gene serves as an effective marker for characterizing carbapenem-resistant S. marcescens carrying blaKPC, confirming that the outbreak was caused by the clonal expansion of isolates harboring blaKPC on an IncP6 plasmid.